Simulasi Tekanan Menggunakan Program Watercad Pada Sistem Pendistribusian Air Bersih Di Pdam Tirta Musi Palembang - Mega Yunanda; Ferry Kurniawan (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
District Meter Area (DMA) filtering is one of the DMA located in the 3 Ilir service Unit region, with 2013 customers as much as 1,392 subscription connections and 2017 as many as 1,490 subscription connections. The purpose of research is to know the water needs in 2018, customer growth projection, water needs 5 years ahead, high loss of press on pipelines and pressure on the pipeline network of clean water distribution. The research site is Jl. Penyaringan, Lr. Tirto Mulyo, Jl. Bambang Utoyo Kiri, Lr. Sahabat, Lr. Bugis, Lr. Sianjur III, with a different high contour and wide area. The method used is Hadry Cross method and pressure simulation using WaterCAD program. The result of clean water needs analysis in 2018 is 33.027 lt/sec. Projected customer growth period of 5 years to the future (year 2022) is 2,362 subscription connection, the amount of clean water needs of 56.174 lt/sec. High Loss Press (HGS) distribution pipeline network year 2017 is the largest in the block 7 with a high loss of pressure 1.0825 m or 0.10825 atm. The result of the pressure simulation of pipelines using WaterCAD program acquired pressure of 0.7546 ATM at junction Point J-33 block 5 (Lr. Tirta Mulyo) until 1.5149 ATM at junction Point J-68 block 7 (Lr. Bugis).